The Influence of Brand Image and Sales Promotion on Buyers' Decisions in Using Mypertamina as a Transaction Tool - Anggraini, Alia; Widiyanti, Marlina; Saggaff Shihab, Muchsin; Maulana, Ahmad (Pusat Publikasi Nusantara, 2023)
This research aims to determine the influence of brand image and sales promotion on purchasing decisions in using MyPertamina as a means of payment transactions in the city of Palembang. The population in this study is all consumers who make purchases using the MyPertamina application as a means of payment transactions in the city of Palembang in 2023. The sample in this study was 100 respondents using several criteria in determining the sample. The results of multiple linear analysis show that brand image and sales promotion have a positive and significant effect on buyer decisions. Brand image is expected by PT Pertamina Patra Niaga to provide a variety of payment options. Where consumers, especially those over 40 years old, are rather difficult if they need to top up. Sales promotion is expected PT Pertamina Patra Niaga to increase sales promotion by giving discounts / discounts to consumers who make purchases by making payments through the MyPertamina application